Multilocality and Transnationality: New Challenges for Urban Development and Urban Policy - Dittrich-Wesbuer, Andrea; Plöger, Jörg (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
Multilocality and transnationality are important expressions of late-modern lives. A pronounced attachment to more than one place is a common characteristic of the various types discussed by scholars. People are thus increasingly less related to only one (residential) location. This is facilitated through networks between groups and individuals, while differentiated social spaces emerge between the involved places. With regard to urban development, the relevance of these processes has not been fully examined yet. This applies for research as well as for the cities themselves, who only marginally refer to multilocal and transnational phenomena in their strategies and actions and continue to adhere to a territorial logic. The quantitative and qualitative significance, however, does call for a more thorough consideration in the context of urban governance. This contribution outlines some of the consequences of these processes for urban development and specifies approaches that consider the changing patterns of spatial-temporal behaviour.